Role of dopant ions in electrocatalytic oxidation of methanol using conducting polypyrrole electrodes - Radhakrishnan, S.; Adhikari, Arindam (Journal of Power Sources, 2006)
Conducting polypyrrole electrodes obtained by electro-polymerization of pyrrole on vacuum metallized glass substrates are modified by doping with a range of metal halides as dopant ions having different electronegativity. Electro-oxidation of methanol using these electrodes is studied by means of cyclic voltammetry in 0.1 M HCiO(4) as supporting electrolyte. It is found that the electronegativity of the dopant ion plays a very important role in the electrocatalytic activity. Polypyrrole doped with zirconium chloride gives the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. The results are explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which is associated with the acceptor state created by the dopant in the semi-conducting polymer. (c) 2005 Published by Elsevier B.V.
Keywords: conducting polymers; electrocatalysis; fuel cells; Methanol oxidation; polypyrrole